The general model of Malaysian households housing budget - Khalid, Halim; Hashim, Haslifah; Mohamad, Massita; Khalid, Kamal; Khalid, Kamil (2012)
﻿There is endless story about the important of housing for human being. Not just one of basic need for human kind, but it provides additional life style value to them. Most of housing practices in Malaysia may classified into four periods that reflect to housing budget needs during renting a room or during renting a house, during buying a house and during living after payment of mortgage loan has been completed. In Malaysia, peoples buy houses through mortgage loans which protected by Mortgage Reducing Term Assurance (MRTA). The buyers with such insurance coverage will benefits from risk of losing the house especially if they die later. This helps their beneficiaries maintain their standard of living in term of housing needs. But, other sad story heard from people who currently renting a house. If the breadwinner of the family die, then their family would face trouble maintaining their housing needs today and lost opportunity to own or buy a house at least relatively equal to current standard of living if their breadwinner doesn’t die today. It is important to have a model of households housing budget for Malaysian which include the housing periods in order to induce sufficient amount of funds for such needs. So that every beneficiary in Malaysia would never experience depreciating in housing standard of living if they know the exact amount of funds needed throughout their mysterious years. This paper will propose the model and its variables that consistent with Malaysian law environments, common practices and the stages of family life cycle.